2018
DOI: 10.1096/fj.201700610rr
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the localization and exploring a functional role for Gprc5c in the kidney

Abstract: The investigation of orphan GPCRs (GPRs) has the potential to uncover novel insights into whole animal physiology. In this study, our goal was to determine the renal localization of Gprc5c, a receptor that we previously reported to be highly expressed in murine whole kidney, and to examine physiologic parameters in Gprc5c knockout (KO) mice to gain insight into function. Gprc5c localized to the apical membrane of renal proximal tubules (PTs) in mice, rats, and humans. With the comparison of Gprc5c wild-type (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
2
17
1
Order By: Relevance
“…One of the proteins detected, GPRC5C (G protein‐coupled receptor class C group 5 member C), was detected only in the apical sample. GPRC5C is an orphan receptor that belongs to the GPRC5 family (Robbins et al, 2000) and is involved in renal acid–base homeostasis (Rajkumar et al, 2018), but it had never been reported as an exosome protein. GPRC5C was detected in the apical PEG pellet alone (Fig 2C) and floated into Fr.…”
Section: Resultsmentioning
confidence: 99%
“…One of the proteins detected, GPRC5C (G protein‐coupled receptor class C group 5 member C), was detected only in the apical sample. GPRC5C is an orphan receptor that belongs to the GPRC5 family (Robbins et al, 2000) and is involved in renal acid–base homeostasis (Rajkumar et al, 2018), but it had never been reported as an exosome protein. GPRC5C was detected in the apical PEG pellet alone (Fig 2C) and floated into Fr.…”
Section: Resultsmentioning
confidence: 99%
“…Using a TaqMan GPCR array card, we initially identified Gprc5c as being highly expressed in the murine kidney (17). Recently, we investigated further to identify the localization and physiological role of Gprc5c in the kidney (18). As determined by both immunohistochemistry and X-gal staining, Gprc5c localizes specifically to the apical membrane of renal proximal tubules of mice.…”
Section: Gpcr Family C Group 5 Member Cmentioning
confidence: 99%
“…Gprc5c KO mice have reduced blood pH and elevated urine pH. 26 expression, highly expressed in health, is significantly reduced only two weeks following 5/6Nx in rats. 28,29 Our immunohistochemistry analysis of NHE3 expression ( Figure 2C) is consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%